Literally ‘a jerk’: an experimental investigation of expressives in predicative position - Filippo Domaneschi; Bianca Cepollaro; Isidora Stojanovic (Language and Cognition)
The semantic literature on negative expressive terms, such as ‘bastard’ and ‘jerk’, converges on two assumptions. First, the content associated with expressives is attitudinal; more precisely, it amounts to the condition that the agent (typically the speaker) has a negative attitude toward the target (that is, the person referred to with the expressive). Second, the use of such terms is felicitous as long as this condition is satisfied, regardless of whether this information is in the contextual background or not. This assumption has been challenged by Cepollaro, Domaneschi and Stojanovic (2021, Synthese), whose experimental studies show that negative expressives impose constraints on the context, contrary to what had been taken for granted in the literature. In line with their work, our goal is to investigate the first assumption on empirical grounds. Our studies show that when person A calls person B ‘a jerk’, participants prefer the target-oriented interpretation (that B must have done something bad) to the attitudinal agent-oriented interpretation (that A has a negative attitude toward B). Additionally, our studies replicate the main results from Cepollaro, Domaneschi and Stojanovic, 2021, Synthese), as well as reveal some unexpected asymmetries between positive and negative evaluative terms, which were used as control items.